Analyzing the Economic Effects of Electronic Word of Mouth and Brand Image on Impulsive Buying through Crowd Attractiveness - Kamila W, Bunga Nailul; Kurniawan, Brahma Wahyu (Yayasan Riset dan Pengembangan Intelektual, 2025)
In this study, The development of the fast-food culinary industry in Indonesia has shown significant growth in line with the increasingly practical lifestyle of society. Fast food, particularly crispy chicken, has become a popular choice due to its convenience and taste. The intense competition in the culinary business, especially in shopping centers, drives entrepreneurs to create strategies that attract consumer interest. One of the consumer behaviors often utilized is impulsive buying, which refers to unplanned purchasing decisions influenced by environmental stimuli. Factors such as product appearance, promotions, electronic word of mouth (e-WOM), brand image, and crowd attraction play an important role in shaping this behavior. e-WOM contributes to forming initial consumer expectations, while brand image builds positive perceptions of the product. However, both require the support of crowd attraction as a mediating variable, functioning as a social cue that strengthens consumer confidence in making impulsive purchases. This study focuses on PokPok My Crispy Snack at Kediri Mall, which has established a strong reputation in the fast-food industry. The findings are expected to provide insights into the factors influencing impulsive buying behavior in the modern culinary business.